(untitled) (Applied Biological Research, 2025)
Detecting estrus in goats becomes a challenging task in the absence of male goats, as behavioural signs of estrus are often subtle and easily missed. Traditional methods such as visual observation of physiological changes like vulvar edema and cervical mucus discharge may not always be reliable. To address this, the present study aimed to evaluate the efficacy and establish reference values of vaginal electrical resistance (VER) for estrus detection in goats. A total of six goats (N = 6) were used, with their estrus cycles synchronized using progesterone sponges. Behavioural and physiological signs of estrus (viz., buck interest, cervical mucus, and vulvar oedema) and VER were monitored for 22 days, extending through the subsequent estrus cycle. The results revealed significantly lower (P < 0.001) VER values during estrus as compared to other phases of the estrus cycle. The VER values recorded in units (10 units = 1 Ohm) observed during estrous cycle phases were 262.50 ± 12.28 in estrus, 501.33 ± 60.59 in metestrus, 535.64 ± 63.17 in diestrus, and 488.33 ± 51.37 in proestrus. Further, PCA analysis revealed that buck interest and VER values play a more significant role in estrus detection as compared to cervical mucus and vulvar edema. Also, VER across the estrus phase strongly correlated with the physiological estrus signs viz. buck interest and vulvar edema. Based on these findings, we conclude that a reference minimum VER value of 300 units (30 Ω) could be used for estrus detection in Black Bengal and other small-sized goats.